Strain-Engineered Metal-to-Insulator Transition and Orbital Polarization in Nickelate Superlattices Integrated on Silicon - Chen, Binbin (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 The Authors. Advanced Materials published by Wiley-VCH GmbH.